Potensi Wisata Alam Di Pematang Tanggang Desa Negeri Kecamatan Kelumbayan Kabupaten Tanggamus - Bobby Affandy; Agus Setiawan; Duryat Duryat (Jurnal Sylva Lestari, 2016)
Pematang tanggang has a lot of potential tourism resources. However there is no sufficient information about the aspects supporting the area to be developed as a tourist destination. The aims of the study were to examine the potential and natural touristic attraction in pematang tanggang, and to calculate the beauty value of those potential. Direct observation and interview were employed as the data collection methods, accidental sampling was used as the respondent determined. Scenic beauty estimation and descriptive analysis were emplayed as data analysis method. The results of the study shows that the potential and the natural touristic attraction in Pematang Tanggang are; Tanggang waterfall, Payung waterfall, view to the Lampung bay, and wolf tree. Activities could be done are encamped, photography, bird watching, primate watching, and rock climbing. Based on the scenic beauty estimation method the value of potential and natural touristic attraction in Pematang Tanggang from the higest to the are; Tanggang waterfall (33), Payung waterfall (20), view to the Lampung bay (4), and wolf tree (0). Keywords: nature potential, Pematang Tanggang, scenic beauty estimation